Democracy's Literature: Politics and Fiction in America - Deneen, Patrick J.; Romance, Joseph (Rowman & Littlefield Publishers, 2005)
American literature is profoundly, almost inescapably political. America's most thoughtful authors long ago realized that it was through the novel, the novella, and the story that philosophic education of America's citizens would best be undertaken. In this fascinating new anthology of original essays, ten leading scholars explore the ways in which American civic education has been informally advanced through literature. Delving into the works of authors ranging from Mark Twain to William Faulkner to Octavia Butler, these essays reflect on the close relationship between democracy and literature. They convey an understanding that the greatest American literary works are also works of profound philosophical insight. Through careful analysis, Democracy's Literature illustrates that democracy and literature are natural partners, forging a relationship that America's greatest authors have long realized in their subtle efforts to craft a democratic public philosophy.